Creatine kinase isoenzyme activity during and after an ultra-distance (200 km) run - HJ Son; YH Lee; JH Chae; CK Kim (Termedia Publishing House, 2016)
lt is commonly assumed that creatine kinase (CK) activity in plasma is related to the state of an inflammatory response at 24-48 h, and also it has shown biphasic patterns after a marathon run. No information is available on CK isoenzymes after an ultra-marathon run. The purpose of the present study is to examine the CK isoenzymes after a Z00 km ultra-marathon run and during the subsequent recovery. Blood samples were obtained during registration 1 2 h before the 200-km race and during the race at 100 km, 150 km and at the end of 200 km, as well as after a 24 h period of recovery. Thirty-two male ultra-distance runners participated in the study. Serum CPK showed a marked increase throughout the race and 24 h recovery period (p<0.001). Serum CK during the race occurs mostly in the CK-MM isoform and only minutely in the CK-MB isoform and is unchanged in the CK-BB isoform. High-sensitivity C-reactive protein (hs-(RP), oestradiol, AST and ALT increased significantly from the pre-race value at 100 km and a further increase took place by the end of the 200 km run. The results of our study demonstrate a different release pattern of creatine kinase after an ultra-distance (200 km) run compared to the studies of marathon running and intense eccentric exercise, and changes in several biomarkers, indicative of muscle damage during the race, were much more pronounced during the latter half (100-200 km) of the race. However, the increases in plasma concentration of muscle enzymes may reflect not only structural damage. but also their rate of clearance.